Exploration of Feminist Consciousness in Ashapoorna Devi‘s Novels the First Promise and Subarnalata - Chaudhary, Kajal; Vashist, Shivani (International Journal of Psychosocial Rehabilitation, 2020)
It is really difficult for a woman to begin her journey towards success, as she has to struggle extremely owing to the complexities of life. Each woman is suppressed by the patriarchal society. Though a woman has her own identity and individuality, she is considered a ‘subaltern’ or ‘second sex,’ and her voice is repeatedly silenced by society. But in the contemporary dynamic world, boundaries are being challenged, and the voiceless subaltern of the bygone era refuses to be a mute spectator to the marginalization. Women make themselves recognizable through their acts of retaliation and resistance against the hegemonic power structure. Vivid shades of women’s lives and their plight are revealed through Indian women novelists’ writings. Ashapurna Devi is one such Bengali woman writer who has made a remarkable contribution by depicting the determined and individualized women who exhibit a strong spirit to fight against all odds. The research paper analyzes the narratives of resistance and resilience of women in hegemonic setups in Ashapurna Devi’s novels The First Promise and Subarnalata. The novels present the suppressed position of women and their longing struggle to ascertain identity. The aim of my paper is not only to depict the helplessness, exploitation, and violence meted out to the oppressed women but also to exhibit their never-say-die spirit against all odds. In this paper, I seek to bring out the significance of these novels in providing valuable glimpses of women’s experiences of oppression, protest, and awakening of feminist consciousness.